Analisis Pengaruh Right Issue Dan Dividen Terhadap Pergerakn Harga Saham Di Bursa Efek Indonesia (Studi Kasus KOMPAS100) - Didik Swan Budi Utomo; Muhammad Imron; Andik Susanto (JAMER : Jurnal Akuntansi Merdeka, 2022)
The purpose of investors investing in the capital market is to obtain rewards or income from the funds invested. Investors who invest their funds in a company's shares aim to earn income in the form of dividends and returns. This study aims to analyze the effect of right issue and dividend announcements on stock price movements between before and after the announcement date of rights issue and dividends, and analyze the effect of right issue and dividend announcements on expected stock returns. The population of this study amounted to 10 companies that issue rights issues and dividends on the KOMPAS100 Index which are listed on the Indonesia Stock Exchange (IDX). The sampling technique used was purposive sampling. The sample used is companies that issue rights issues and dividends in the period 2016-2020. The data analysis technique in hypothesis testing was carried out using the paired sample t-test difference test because the data were normally distributed. The results of this study indicate that there is no significant effect of the rights issue on stock price movements. As for dividends, it shows a significant difference to stock price movements.